Donated materials in assisted reproductive technologies: an ethico-legal analysis of art legislations worldwide - Zawawi, Majdah (Tehran University of Medical Sciences, 2010)
This paper provides an appraisal of countries that have legislations pertaining to assisted reproductive technologies (ART). In doing so, the paper highlights the emphasis on the protection of reproductive freedom of the couples seeking ART treatment. This belief is grounded primarily on the basic notion of liberalism that attaches primary importance to respect for individual freedom, which is the foundation of the notion of reproductive rights as understood by western standards today. The main aim of the appraisal is to see how these legislations address the drastic changes in familial relationships when ART involves the use of donated materials.